Numerical investigation on flow characteristics of water in the fish tank on a force-rolling aquaculture platform. (1st December 2020) - Guo, Xiaoyu; Li, Zhisong; Cui, Mingchao; Wang, Benlong
Abstract: The fishing platform is expected to be a sustainable method for offshore aquaculture, which can avoid fish escapes by using tanks in harsher sea state and meanwhile make use of natural water. In this paper, the flow characteristics (residence time, velocity uniformity) in a force-rolling aquaculture tank are numerically investigated and analyzed by statistical methods. Through our simulations, we find that water inlet and drainage play a limited role in accelerating water velocity magnitude when being compared with the effect of the roll. Roll accelerates the velocity magnitude of water in the tank and shortens the circulation time. For cases with different rolling angles, the magnitude of water velocity in the tank is very sensitive to the rolling angle and increases with it; for cases with different rolling periods, velocity magnitude decreases as rolling periods increase. Moreover, if the rolling period exceeds a threshold, such as 10 s in this paper, the velocity increment is tiny. The residence time of water in the tank seems insensitive to both rolling angle and period. For all simulations, there is a low-velocity region along the rolling axis in the middle of the fishing tank. The water inlet slightly affects the volume of this low-velocity zone. Highlights: Flow characteristics were numerically investigated in a force-rolling sloshing tank. The influence of rolling angles and periods were studied under typical sea states. Statistical methods were employed to analyze water velocity and residence time for fish welfare in aquaculture. Flow characteristics summarized in this paper are helpful to the application of the aquaculture platform.